A new variety of Erythroxylum ulei from the Cordillera Escalera of Peru (Archerythroxylum, Erythroxylaceae) - White, Dawson M. (Phytotaxa, 2020)
Erythroxylum ulei var. escalerense is a new variety described from a single collection made in a remote region of the Cordillera Escalera in Loreto, Peru. It is an understory shrub exhibiting the erect lateral setae on the stipules and ovoid fruits characteristic of E. ulei, but with much smaller, narrowly elliptic to lanceolate leaves without bifacial coloration. Morphological comparison and phylogenetic relationships with similar Erythroxylum are presented and discussed, as well as implications for the current intrageneric classification system.